BIOACCUMULATION OF METALS AND EVALUATION OF GOLDEN MUSSELS ENCRUSTED ON DIFFERENT SCREENS OF NET CAGES - Mateus Antonio BESEN; Nilton Garcia MARENGONI (Boletim do Instituto de Pesca)
This study aimed to evaluate the characterization and bioaccumulation of metals of the golden mussel encrusted in the screens of net cages installed in the reservoir of Itaipu Binacional. The experimental design was completely randomized, composed of two types of screens (PVC and Bezinal) distributed on four sides (Sides I, II, III, and IV) of the net cage. The total mass, the average mass, and the dimensions (width, height, and length) of the mollusks were evaluated. The mussels adhered to the Bezinal screen presented a higher average mass, length, height, and width than those colonized on the PVC screen (p <0.05). However, the PVC screen provided a greater (p <0.05) total mass of encrusted mussels. Regardless of the screen used, the average mass and length of mussels had higher values on Side I (p <0.05) than to the Sides II and IV, but not different from Side III. The mussels evaluated showed high levels of metals, and those encrusted in the Bezinal screen presented higher levels of Al, Zn and Cr than the individuals on the PVC screen (p <0.05). The use of a Bezinal screen is more efficient than a PVC screen, as an antifouling material. Mussels with shorter lengths had a higher incidence on the PVC screen. The mussels encrusted in the Bezinal screen bioaccumulate higher content of Al, Zn, and Cr. The type of screen used in the net cages influences the mass and size of adhered mussels, as well as can interfere with the metal accumulation in the golden mussel.